No Meaning in the Quran: Sukidi's Thought - Yanuri, Yusuf Rohmat; Setiawan, Ahmad Bayu (Universitas Muhammadiyah Surakarta, 2025)
Where do the meanings lie? This is one of the most intriguing questions in Qur'anic studies both in the West and the East. Some scholars say that the meaning of the Qur'an is inherently located in the scripture. Then, Indonesian Salafism came up with the slogan